Outcome of relapsed/refractory diffuse large B-cell lymphoma patients treated with polatuzumab vedotin-based therapy: real-life experience. Issue 1 (2nd January 2021) - Segman, Yafit; Ribakovsky, Elena; Avigdor, Abraham; Goldhecht, Yair; Vainstein, Vladimir; Goldschmidt, Neta; Harlev, Shimrit; Horwitz, Netanel; Gutwein, Odit; Gurion, Ronit; Itchaki, Gilad; Abadi, Uri; et al.
Abstract: The efficacy of polatuzumab vedotin in relapsed/refractory diffuse large B-cell lymphoma outside clinical study are undetermined. This retrospective study examined the efficacy and safety of polatuzumab vedotin administered in real life settings. Forty-seven patients, 31 with de-novo DLBCL and 16 with transformed lymphoma, treated with polatuzumab-based regimen in 14 Israeli centers between June 2018 and November 2019, were included. Median age was 66.1 years (60.4–78.8) and median number of prior lines was 3 (2–7). The overall response rate was 61% ( n = 29), including 40% complete responses ( n = 19) and 21% ( n = 10) partial responses. The median overall survival and progression-free survival were 8.3 months and 5.6 months, respectively. An ECOG PS ≥2 predicted a decreased overall survival ( p = 0.045). Primary refractory vs relapsed disease ( p = 0.005) and transformed vs de-novo DLBCL ( p = 0.039) were associated with shorter PFS ( p = 0.027). Our data show that polatuzumab-based regimen is an effective and tolerable treatment in relapsed/refractory DLBCL.